Guía de un sistema de ejercicios para fortalecer el razonamiento lógico matemático de los estudiantes de educación general básica - Claudio Muñoz, Rafael Reinaldo (2022)
The present work carried out is based on the implementation of a guide of a system of exercises to strengthen the mathematical logical reasoning of students of basic general education, as the problem of our research work, where its general objective is to develop a guide of a system of exercises so that students can strengthen mathematical logical reasoning at the basic education levels, where the beneficiaries will be the students of the fourth year of basic general education of the "Toacaso" Educational Unit, where the methodology of the The research was considered qualitative and non-experimental since we will not be able to modify the bases of the research that are existing or current, in other words, each of the research variables can be maintained to develop methodological strategies to improve the mathematical logical reasoning in students Therefore, the proposal was proposed Our aim is to strengthen the development of mathematical logical reasoning skills at the basic education levels of the educational unit, through the application of a series of exercises with their respective processes and resolution. It can also be said that the results of the diagnosis before applying the proposed proposal had less than 50% low in their mathematical performance, so that, by being able to apply the proposal by the mathematics teacher to the students, an improvement of more than 50% was found. 90%, where students developed their mathematical logical reasoning.